(untitled) (Research, Society and Development, 2023)
Objective: To analyze possible changes in alcohol use between the preoperative and postoperative periods of bariatric surgery. Methodology: A systematic literature review was carried out between January 2015 and July 2020, using the electronic databases MEDLINE, PubMed, LILACS and SciELO, using different combinations of keywords. The studies included in the review were assessed for quality. Fifteen articles were included for analysis, which presented diversity in relation to the types of study, sample size, instruments and sources for data collection. Results: The vast majority analyzed patients undergoing Roux-en-Y Gastric Bypass alone or in conjunction with other surgical techniques. Considering all selected articles, 10 (66.6%) reported at least one indicator related to greater use of alcohol in the postoperative period of bariatric surgery compared to the preoperative period, including articles with larger sample sizes and longer follow-up time postoperative. Conclusion: The importance of analyzing alcohol use before and after bariatric surgery is highlighted, with a view to preventing and treating alcohol use disorders.